IMPROVING BASIC EDUCATION: HEARING THE SILENCED VOICES OF TEACHERS IN BRAZIL - Akkari, A (UPI Press, 2011)
This article aimed at providing an overview of the findings of a joint researchproject of several Swiss and Brazilians institutions on Brazilian basic education. InBrazil, teaching is governed by the Law of Directives and Foundations of NationalEducation (LDB) stipulating that Brazilian schooling has a compulsory length ofnine years of teaching. To measure the progress in basic education of the nationas a whole the Basic Education Development index was created by the BrazilianEducation Minister. The measurement results showed that quantitative developmentof schooling in Brazil needs to go hand in hand with a concern regarding the qualityof education. Besides, analysis indicated necessity of taking into account structuralfactors along with the contributions of fundamental participants, especially teachers.Several teachers’ opinions concerning with current situation were gained. First, indealing with their profession, Brazilian teachers considered that they were lack ofsocial recognition, had incomplete training, and earned insufficient salary. Second,concerning with school, there were distant school-family relations; politicalpedagogicalproject was too far removed from the day-to-day; accountability wasespecially at the administrative level. Third, in connection with class, situationscovered solitude of the teachers, many teachers had given up, and social andfamilial difficulties of the students.Key words: Basic education, teacher, hearing the silence voices